Performance comparison of the floating and fully submerged quasi-point absorber wave energy converters. (August 2017) - Sergiienko, N.Y.; Cazzolato, B.S.; Ding, B.; Hardy, P.; Arjomandi, M.
Abstract: Axisymmetric point absorbers are mostly designed as floating buoys that extract power from heave motion. Power absorption limits of such wave energy converters (WECs) are governed by the displaced volume of the buoy and its ability to radiate waves. In the case of fully submerged WECs, the power performance becomes a function of additional variables including the proximity to the mean surface level of the water, body shape and the maximum stroke length of the power take-off system. Placing the body below the water surface increases its survivability in storm conditions but changes the hydrodynamic properties of the WEC including maximum absorbed power. This paper investigates the differences between floating and fully submerged point absorber converters from the number of perspectives including energy extraction, bandwidth, and optimal size for a particular wave climate. The results show that when compared with floating converters, fully submerged buoys: (i) generally absorb less power at longer wavelengths, (ii) have narrower bandwidth, (iii) cannot be replaced by smaller units of the same total volume without a significant loss of power, and (iv) have a significant advantage as they can effectively utilise several modes of motion (e.g. surge and heave) in order to increase power generation. Highlights: The performance comparison between floating and submerged point absorber wave energy converters is analysed. Submerged converters generally absorb less power than their floating counterparts of equal volume. Submerged converters have narrower bandwidth. The "small is beautiful" statement is not valid for submerged converters. Power absorption from several degrees of freedom is more attractive for submerged converters.